Detection of the recently emerged synthetic cannabinoid 5F-MDMB-PICA in 'legal high' products and human urine samples - Mogler, Lukas; Franz, Florian; Rentsch, Daniel; Angerer, Verena; Weinfurtner, Georg; Longworth, Mitchell; Banister, Samuel D; Kassiou, Michael; Moosmann, Bjoern; Auwärter, Volker (Drug testing and analysis, 2018)
Indole or indazole-based synthetic cannabinoids (SCs) bearing substituents derived from valine or tert-leucine are frequently abused new psychoactive substances (NPS). The emergence of 5F-MDMB-PICA (methyl N-{[1-(5-fluoropentyl)-1H-indol-3-yl]carbonyl}-3-methylvalinate) on the German drug market is a further example of a substance synthesized in the context of scientific research being misused by clandestine laboratories by adding it to 'legal high' products. In this work, we present the detection of 5F-MDMB-PICA in several legal high products by gas chromatography-mass spectrometry (GC-MS) analysis. To detect characteristic metabolites suitable for a proof of 5F-MDMB-PICA consumption by urine analysis, pooled human liver microsome (pHLM) assays were performed and evaluated using liquid chromatography-tandem mass spectrometry (LC-MS/MS) and liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QToF-MS) techniques to generate reference spectra of the in vitro phase I metabolites. The in vivo phase I metabolism was investigated by the analysis of more than 20 authentic human urine specimens and compared to the data received from the pHLM assay. Biotransformation of the 5-fluoropentyl side chain and hydrolysis of the terminal methyl ester bond are main phase I biotransformation steps. Two of the identified main metabolites formed by methyl ester hydrolysis or mono-hydroxylation at the indole ring system were evaluated as suitable urinary biomarkers and discussed regarding the interpretation of analytical findings. Exemplary analysis of one urine sample for 5F-MDMB-PICA phase II metabolites showed that two of the main phase I metabolites are subject to extensive glucuronidation prior to renal excretion. Therefore, conjugate cleavage is reasonable for enhancing sensitivity. Commercially available immunochemical pre-tests for urine proved to be unsuitable for the detection of 5F-MDMB-PICA consumption. Copyright © 2017 John Wiley & Sons, Ltd.